Association between polymorphisms of insulin and insulin receptor gene with childhood obesity in Malay population - Pey, Christinal Wen Teh; Nurul Adibah Nizam,; Pei, Nee Chong; Abdul Rahman Jamal,; Bee, Koon Poh; Wan Zurinah Wan Ngah, (Penerbit UKM, 2016)
Childhood obesity is a global epidemic, which leads to the increasing number of studies on genetic locations associated with obesity-related traits. Polymorphisms of insulin (INS) gene have been shown to be associated with obesity-related phenotypes in Europeans; while insulin receptor (INSR) gene has been associated with energy regulation. Therefore, this study was conducted to investigate the association between the INS (rs689) and INSR (rs3745551) gene polymorphisms with childhood obesity risk in a Malay childhood population. Normal weight (538) and overweight or obese (557) children aged 6-12 years old were genotyped using semi-automated Sequenom iPLEX® Gold. Body mass index (BMI) was calculated from measured body weight and height. The rs689 (T/T: 0.006, A/T: 0.159 and A/A: 0.835) and rs3745551 (G/G: 0.054, A/G: 0.378 and A/A: 0.568) genotype distributions were consistent with Hardy Weinberg equilibrium. The T-minor allele frequency for rs689 was 8.6% and G-minor allele frequency for rs3745551 was 24.3%. Minor allele of INS gene polymorphisms significantly increased risk of obesity among Malay children (sex- and age-adjusted OR=1.580; 95%CI: 1.134-2.201). However, INSR gene polymorphisms were not significantly associated with childhood obesity. In conclusion, the polymorphisms of INS gene, rather than INSR gene, were associated with childhood obesity in the Malay population.